Application of Walimah Infiṣal According to Islamic Law - Fahmi Fatwa Rosyadi Satria Hamdani; Daniah Daniah; Muhammad Yunus; Hudzaifah Muhammad Maricar (At-Taqaddum, 2022)
At weddings, after the marriage contract is carried out, Muslims are encouraged to hold a walimatul 'ursy, or what is also known as a banquet. In holding a walimatul 'ursy, there are procedures so that it is by Islamic law. In Islam, it has been regulated that the lives of men and women are separate, meaning that no mixing (ikhțilat) is permitted, and it has been explained in the Al-Qur'an and hadith regarding the harm that occurs if you give khțilat. It must also be applied during the walimatul 'ursy. The separation between men and women in the walimatul 'ursy is called walimah infiṣal. This research aims to find out the views of Islamic law regarding walimah infiṣal. This research uses qualitative methods with a case study approach, and the researcher took four wedding organizers from the PANATACARA organization in Bandung City for research. The research results show that the implementation of walimah infiṣal is highly recommended to avoid mixing between men and women who are not mahram. This is carried out in three ways, namely separating the aisle, separating guests, and separating the food buffet between men and women.At weddings, after the marriage contract is carried out, Muslims are encouraged to hold a walimatul 'ursy, or what is also known as a banquet. In holding a walimatul 'ursy, there are procedures so that it is by Islamic law. In Islam, it has been regulated that the lives of men and women are separate, meaning that no mixing (ikhțilat) is permitted, and it has been explained in the Al-Qur'an and hadith regarding the harm that occurs if you give khțilat. It must also be applied during the walimatul 'ursy. The separation between men and women in the walimatul 'ursy is called walimah infiṣal. This research aims to find out the views of Islamic law regarding walimah infiṣal. This research uses qualitative methods with a case study approach, and the researcher took four wedding organizers from the PANATACARA organization in Bandung City for research. The research results show that the implementation of walimah infiṣal is highly recommended to avoid mixing between men and women who are not mahram. This is carried out in three ways, namely separating the aisle, separating guests, and separating the food buffet between men and women.